Respostas
respondido por:
1
a) f(x) = -x² + x
f(0)= -0² + 0
f(0)=0 + 0
f(0)= 0
b) Se x for igual a -1 o resultado da função vai ser igual a:
f(-1)= -(-1)²+(-1)=
= - (1) -1
= -1 -1
= -2 ou seja: - 0 ( menor que 0)
f(0)= -0² + 0
f(0)=0 + 0
f(0)= 0
b) Se x for igual a -1 o resultado da função vai ser igual a:
f(-1)= -(-1)²+(-1)=
= - (1) -1
= -1 -1
= -2 ou seja: - 0 ( menor que 0)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás